2020
DOI: 10.1002/pen.25481
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel control strategy for a highly segmented injection mold tempering for inline part warpage control

Abstract: The demand of precise injection-molded parts is steadily increasing and is today one of the most relevant challenges, due to local variations in temperature and pressure during the production of the part. These variations can lead to a significant change of the local specific volume, shrinkage potential, and inner stress, which ultimately results in part warpage. By homogenizing the local specific volume over the part according to the specific pvT-behavior of the polymer, warpage is expected to be reduced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…This work therefore aims modify local temperatures, such that melt properties can be homogenized to reduce stresses, eliminating part warpage for different materials. In our previous works, we demonstrated that a model predictive control yielded parts with significantly higher control accuracy and reproducible part warpage compared to a PID-controller [14,15]. Since the model predictive control is based on a self-developed simulation of the part temperature (based on Fourier's law in one dimension), the same input parameters always result in the same output parameters for the power to control the temperature (see discussion in Section 2.3).…”
Section: Introductionmentioning
confidence: 99%
“…This work therefore aims modify local temperatures, such that melt properties can be homogenized to reduce stresses, eliminating part warpage for different materials. In our previous works, we demonstrated that a model predictive control yielded parts with significantly higher control accuracy and reproducible part warpage compared to a PID-controller [14,15]. Since the model predictive control is based on a self-developed simulation of the part temperature (based on Fourier's law in one dimension), the same input parameters always result in the same output parameters for the power to control the temperature (see discussion in Section 2.3).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] More than 30% of plastic parts are molded by the IM process. [4,5] The repeatability accuracy of the part weight is a comprehensive evaluation standard reflecting the performance of an IMM. The injection velocity, pressure, temperature, and other machine parameters of modern IMMs today can be controlled and characterized by high accuracy and repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Injection molding (IM) is one of the most suitable methods for the mass production of plastic parts with complicated shapes. [ 1, 2 ] During the injection molding process, the molten plastic flows into the mold cavity and then cools and solidifies. Considering its importance in a molding machine, the clamping unit requires a high clamping force (CF) to firmly hold the mold halves to withstand the plastic melt pressure inside the mold cavity.…”
Section: Introductionmentioning
confidence: 99%